Improving the Thermostability and Catalytic Activity of an Inulosucrase by Rational Engineering for the Biosynthesis of Microbial Inulin - TOKSOY ÖNER, EBRU (AMER CHEMICAL SOC, 2021)
Thermostability and enzymatic activity are two vital indexes determining the application of an enzyme on an industrial scale. A truncated inulosucrase, Laga-IS Delta 138-702, from Lactobacillus gasseri showed high catalysis activity. To further enhance its thermostability and activity, multiple sequence alignment (MSA) and rational design based on the modeled structure were performed. Variants A446E, S482A, I614M, and A627S were identified with an improved denaturation temperature (T-m) of more than 1 degrees C. A combinational mutation method was further carried out to explore the synergistic promotion effects of singlepoint mutants. Additionally, 33 residues at the N-terminus were truncated to construct mutant M4(N-33). The half-life of M4(N-33) at 55 degrees C increased by 120 times compared to that of Laga-IS Delta 138-702, and the relative activity of M4(N-33) increased up to 152% at the optimal pH and temperature (pH 5.5 and 60 degrees C). Molecular dynamics (MD) simulations illustrated the decreased b-factor of the surface loop of M4(N-33).
Keywords: inulosucrase; rational design; thermostability; enzymatic activity; molecular dynamics simulation; MOLECULAR-WEIGHT INULIN; LACTOBACILLUS-REUTERI; CHAIN-LENGTH; PROTEINS; ENZYMES; EXPRESSION; FRUCTANS; INSIGHTS; SUCROSE